Diseño de un modelo de gestión de calidad para mejorar la eficiencia en los procesos productivos en la carpintería EL ARBOLITO. - Tandalla Pullotásig, Javier Darwin (2018)
"CARPINTERÍA EL ARBOLITO" dedicated to the production and marketing of furniture, place where the researcher pointed out that it does not have a methodology to achieve high productivity in the production area, the activities that have been carried out in the workplace have not been managed efficiently and for this reason this workshop has been immersed in serious problems because it does not have an efficient handling of the raw material that shows the absence of standardization in its processes, which allows performing a quality control in each sub-processes for the elaboration of furniture; the design of a quality management model will let the improvement of the productive processes of each activity carried out by the workshop taking into account the time that is delayed in each process and therefore leads to the development of the efficiency of the workshop, it means higher production and less waste; an inductive methodology was used for this research where the information of the carpentry was collected, also the descriptive analysis was used for the determination of the problem and the identification of activities, that supply a management model as result which allowed to apply norms of security and health for the workshop employees avoiding accidents at work that are determined in the management indicator as the process map which details each function wholly fulfilled with the research techniques developed, this will help the manager to manage with quality philosophy and effectively improve the productive management.